Penentuan Titik Akhir Titrasi yang Tepat untuk Penentuan Kadar Amonium Klorida - Muslim Suardi (LPPM Universitas Abdurrab, 2023)
The end point titration is very important to obtain the accurate analysis. No reference was found related with the end point titration of Mohr’s method. In other hand, the quality of drug is important to ensure efficacy and safety. One of requirement is the contain of the drug. Instability of a drug product related with a decreasing in the quality of the drug in term loss of drug efficacy and may be become toxic. Black Cough Syrup is one of famous cough medicine, in Indonesia called Obat Batuk Hitam (OBH). One of the active substances in OBH is ammonium chloride. The determination of titration point in argentometry should be considered appropriately. The study aims were to determine the exact end point of titration and the levels of ammonium chloride in OBH of 3 preparations available in the market and determine the end point titration. NH4Cl levels were determined using the argentometric titration method. The percentage of ammonium chloride in samples A, B and C were 96.84±1.07, 93.57±1.10, and 97.10±1.10%, respectively. Ammonium chloride levels in all samples fulfill the requirements of official pharmacopeia. The titration point was at once the changing of solution color from pale yellow into reddish brown